A vanadium disulfide thermal battery positive electrode material and its preparation method and application

The vanadium disulfide cathode material prepared by hydrothermal synthesis solves the problem of insufficient performance of existing thermal battery materials under high temperature and high voltage conditions, and achieves the effect of stable voltage and long discharge time of high voltage and long life thermal battery.

CN115799498BActive Publication Date: 2024-12-24BEIJING INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210526292.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-16
Publication Date
2024-12-24
Estimated Expiration
2042-05-16

AI Technical Summary

Technical Problem

The existing thermal battery positive electrode materials exhibit high internal resistance, polarization, poor thermal stability and low voltage platform under high temperature and high voltage conditions, which cannot meet the long-term high voltage stable working needs.

Method used

The vanadium disulfide (VS2) cathode material prepared by hydrothermal synthesis has a spherical structure and high conductivity. By combining it with Li-Si material, a high voltage and long life thermal battery cell is formed.

Benefits of technology

It achieves a stable voltage and a long discharge time when the constant current discharge is discharged at 500°C. It is suitable for high voltage and long life thermal batteries. It has a simple preparation process, low cost, and high material purity. It is suitable for high voltage and long life thermal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115799498B_ABST
    Figure CN115799498B_ABST
Patent Text Reader

Abstract

The present invention discloses a vanadium disulfide thermal battery positive electrode material and its preparation method and application. The vanadium disulfide thermal battery positive electrode material of the present invention has a lamellar flower ball structure, which is composed of concave hexagonal self-polymerization; the diameter range of the lamellar flower ball structure is 4 to 12 μm. The vanadium disulfide thermal battery positive electrode material of the present invention is applied to a thermal battery with Li-Si material as the negative electrode, with an open circuit voltage of 2.1V-2.8V. Under 500°C and 50mA constant current discharge, the first discharge platform is 2V-2.3V, without obvious voltage spikes, and the discharge voltage is stable. When the cut-off voltage is 1V, the discharge time is greater than 54min, with a long duration, and is suitable for long-life thermal batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of positive electrode materials for thermal batteries, and in particular to a vanadium disulfide thermal battery positive electrode material and a preparation method and application thereof. Background Art

[0002] Thermal batteries are disposable heat-activated storage batteries that are activated by using an electric spark to ignite an internal heating agent, melting the electrolyte into an ion conductor, and occupy a very important position in military power sources. At present, the most commonly used positive electrode materials in thermal batteries are transition metal sulfides, among which FeS2 has attracted widespread attention due to its advantages such as low material cost and large specific capacity. It is still the most commonly used positive electrode material in commercial thermal batteries. However, FeS2 itself has a high internal resistance, is prone to polarization during the discharge reaction, and has poor thermal stability and a low voltage platform. Therefore, it cannot well meet the thermal battery's long-term high voltage and stable operation requirements at high temperatures.

[0003] At present, in addition to iron sulfide, other metal sulfides used as positive electrode materials for thermal batteries include molybdenum sulfide, cobalt sulfide, etc. Compared with FeS2, MoS2 has higher thermal stability, but its internal resistance is larger and its voltage platform is low, which cannot meet the needs of high voltage and high power discharge; CoS2 has a higher decomposition temperature than FeS2 and a lower resistivity, but also has a lower potential and is expensive, so it cannot meet the requirements of high voltage.

[0004] With the development of miniaturization and intelligence of weapons, the preparation of high-voltage and long-life positive electrode materials is an important means to increase the voltage of single cells and reduce the size of thermal batteries. It is also the research focus of future power source thermal batteries.

[0005] Therefore, there is a need for a positive electrode material for a thermal battery suitable for high temperature and high voltage. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a vanadium disulfide thermal battery positive electrode material and its preparation method and application. The vanadium disulfide thermal battery positive electrode material of the present invention has a lamellar flower ball structure, which is composed of concave hexagonal self-polymerization. The vanadium disulfide thermal battery positive electrode material of the present invention is applied to a thermal battery with Li-Si material as the negative electrode, and the open circuit voltage is 2.1V-2.8V. Under 500°C and 50mA constant current discharge, the first discharge platform is 2V-2.3V, there is no obvious voltage spike, the discharge voltage is stable, and when the cut-off voltage is 1V, the discharge time is greater than 54min, the duration is long, and it is suitable for long-life thermal batteries. The vanadium disulfide thermal battery positive electrode material of the present invention is completed in one time by a hydrothermal synthesis method, the preparation process is simple, the raw materials are easily available and the cost is low, and it has broad application prospects.

[0007] One of the purposes of the present invention is to provide a vanadium disulfide thermal battery positive electrode material.

[0008] The vanadium disulfide thermal battery positive electrode material has a lamellar flower ball structure, which is composed of concave hexagonal self-polymerization;

[0009] The diameter of the spherical structure of the lamellae is in the range of 4 to 12 μm, preferably 6 to 10 μm; the interlamellar spacing of the lamellae is in the range of 0.01 to 5 μm, preferably 0.2 to 2 μm.

[0010] The second object of the present invention is to provide a method for preparing the positive electrode material of vanadium disulfide thermal battery which is one of the objects of the present invention.

[0011] The method comprises:

[0012] The sulfur source, vanadium source, alkaline regulator and deionized water are mixed evenly and reacted, and then the reactants are collected, washed alternately with deionized water and an organic solvent, and then dried to obtain the vanadium disulfide thermal battery positive electrode material.

[0013] In a preferred embodiment of the present invention,

[0014] The sulfur source is at least one of thioacetamide and sodium thiosulfate; and / or,

[0015] The vanadium source is at least one of sodium orthovanadate and ammonium metavanadate; and / or,

[0016] The alkaline regulator is at least one of ammonia water, sodium hydroxide solution and sodium carbonate solution; and / or,

[0017] The organic solvent is anhydrous ethanol or carbon disulfide.

[0018] In a preferred embodiment of the present invention,

[0019] The alkaline regulator adjusts the pH of the reaction system to 10-11.

[0020] In a preferred embodiment of the present invention,

[0021] The molar ratio of the sulfur source to the vanadium source is 3:1 to 8:1, preferably 4:1 to 5:1; and / or,

[0022] The mass ratio of the vanadium source to deionized water is 1:100 to 1:180, preferably 1:110 to 1:130; and / or,

[0023] The mass ratio of the alkali regulator to deionized water is 1:10 to 1:25.

[0024] The deionized water in the above mass ratio range of vanadium source to alkali regulator to deionized water refers to deionized water uniformly mixed with sulfur source, vanadium source and alkali regulator, and does not include deionized water for washing reactants.

[0025] In a preferred embodiment of the present invention,

[0026] The reaction temperature is 150 to 200° C., preferably 150 to 180° C., more preferably 180° C., and the reaction time is 19 to 25 hours, preferably 21 to 23 hours, more preferably 22 hours.

[0027] In a preferred embodiment of the present invention,

[0028] The drying temperature is 80-90°C and the drying time is 20-24 hours.

[0029] The third object of the present invention is to provide a high-voltage and long-life thermal battery single cell, using the vanadium disulfide thermal battery positive electrode material of one of the objects of the present invention or the vanadium disulfide thermal battery positive electrode material prepared by the method of the second object of the present invention as the positive electrode material.

[0030] The high-voltage and long-life thermal battery single cell is prepared from a negative electrode, an electrolyte, a vanadium disulfide thermal battery positive electrode material and a nickel (Ni) current collector;

[0031] The negative electrode is preferably at least one of lithium silicon alloy powder and lithium boron alloy powder; and / or,

[0032] The electrolyte is preferably at least one of a solid LiF-LiCl-LiBr ternary all-lithium electrolyte and a solid LiF-LiCl-KCl ternary electrolyte; and / or,

[0033] The nickel current collector is a pure nickel sheet, preferably a φ16 round pure nickel sheet, with a thickness of 0.01 to 2 mm, preferably 0.1 to 1 mm; and / or,

[0034] The mass ratio of the negative electrode to the vanadium disulfide positive electrode material is 1:1 to 1.5:1; and / or,

[0035] The mass ratio of the electrolyte to the vanadium disulfide positive electrode material is 1.5:1 to 2:1.

[0036] Preferably,

[0037] The mass of the vanadium disulfide positive electrode material is 0.1-0.3 g.

[0038] The fourth object of the present invention is to provide a method for preparing a high-voltage and long-life thermal battery cell according to the third object of the present invention.

[0039] The method comprises:

[0040] In an inert atmosphere of a glove box, a negative electrode, an electrolyte, and a vanadium disulfide thermal battery positive electrode material are sequentially added into a cylindrical stainless steel mold, and after being pressed into a cylinder, nickel current collectors are placed on both sides of the cylinder to obtain the high-voltage and long-life thermal battery single cell.

[0041] Preferably,

[0042] After adding the negative electrode, electrolyte, and vanadium disulfide thermal battery positive electrode material to the cylindrical stainless steel mold in sequence, they are all flattened with a pressing rod to avoid unclear boundaries between layers.

[0043] In a preferred embodiment of the present invention,

[0044] The cylindrical stainless steel mold is a φ16 stainless steel cylindrical mold; and / or,

[0045] The pressure of the compression molding is 10-12 MPa, and the time is 10-20 seconds.

[0046] The present invention can adopt the following specific technical solutions:

[0047] The present invention obtains vanadium disulfide thermal battery positive electrode material by hydrothermal synthesis, and its preparation method preferably includes the following steps:

[0048] 1) Material pretreatment: weigh the vanadium source according to the amount, add the deionized water and alkali regulator in the amount, fully dissolve the vanadium source by magnetic stirring, then add the sulfur source in the amount, and fully stir until a clear solution is obtained.

[0049] 2) Hydrothermal synthesis: The pretreatment solution mixed uniformly in 1) was transferred to a 100 ml Teflon-lined stainless steel autoclave. After the stainless steel autoclave was completely sealed, it was placed in a forced air drying oven at 150-200° C. and taken out after reacting for 19-25 hours.

[0050] 3) Washing and drying: After the reaction in 2) is completed, the reactor is taken out and cooled naturally to room temperature, the generated black precipitate is collected, and it is washed three times with deionized water and an organic solvent alternately, and the solid product is collected by centrifugation after each washing. It is placed in a forced air drying oven at 80-90°C and dried for 20-24 hours.

[0051] Beneficial effects of the present invention:

[0052] The vanadium disulfide thermal battery cathode material prepared by the present invention is a two-dimensional transition metal sulfide (TMDs) having a hexagonal crystal layered structure, high conductivity and two-dimensional ion permeation channels, high theoretical potential, and potential as a high-voltage cathode material. Theoretical calculation studies have shown that when discharged to 1.0V, each vanadium disulfide lattice can embed two lithium ions, and the theoretical specific capacity can reach 466mAh·g -1 .

[0053] The invention adopts the positive electrode material obtained by the hydrothermal synthesis method, and the size, shape and composition of the powder can be controlled, while eliminating the high-temperature calcination and grinding process, so that the prepared material has high purity and complete crystal structure, thereby improving its electrochemical performance as an electrode material.

[0054] In the process of preparing high voltage and long life thermal battery cells, use The stainless steel cylindrical mold is added in batches under the inert atmosphere of the glove box. The order of adding negative electrode, electrolyte, and positive electrode is adopted to make the edge boundary of the thermal battery single cell obvious and not easy to short-circuit. The applied pressure is 10-12MPa for one-piece molding, which is easy to operate. The use of Ni collector is more conducive to protecting the single cell structure and providing a good discharge path.

[0055] The thermal battery monomer cell prepared by the vanadium disulfide positive electrode material provided by the present invention has no obvious voltage spike, and the constant current discharge voltage is stable and the time is long. Therefore, the vanadium disulfide thermal battery positive electrode material of the present invention is suitable for high-voltage and long-life thermal batteries. The positive electrode material prepared by the present invention is completed once by a hydrothermal synthesis method, the preparation process is simple, the raw materials are easily available, the cost is low, the repeatability is high, and it has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 The figure is an X-ray diffraction (XRD) diagram of the positive electrode material of the vanadium disulfide thermal battery in Example 1. The spectrum in the lower part of the figure is the spectrum of the VS2 standard card, and the spectrum in the upper part of the figure is the spectrum of the X-ray diffraction of the positive electrode material of the vanadium disulfide thermal battery in Example 1;

[0057] Figure 2 This is a scanning electron microscope (SEM) image of the vanadium disulfide thermal battery positive electrode material of Example 1;

[0058] Figure 3 It is a schematic diagram of the left view of a single cell of a high-voltage long-life thermal battery, in which 1 represents the negative electrode, 2 represents the electrolyte, 3 represents the positive electrode, and 4 and 5 represent nickel current collectors;

[0059] Figure 4This is a comparison graph of the constant current discharge curves at 500°C at 50mA for a thermal battery prepared using vanadium disulfide as the positive electrode material for a thermal battery prepared in Example 1 of the present invention and a thermal battery prepared using iron sulfide material (FeS2) as the positive electrode material for a thermal battery prepared in Comparative Example 1. Curve a in the figure represents the constant current discharge curve of the thermal battery prepared using vanadium disulfide as the positive electrode material for a thermal battery, and curve b in the figure represents the constant current discharge curve of the thermal battery prepared using iron sulfide material (FeS2) as the positive electrode material for a thermal battery. DETAILED DESCRIPTION

[0060] The present invention is described in detail below in conjunction with specific embodiments and drawings. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.

[0061] The raw materials used in the examples are all conventional commercially available raw materials.

[0062] The X-ray diffraction pattern of the vanadium disulfide thermal battery positive electrode material in the present invention is obtained by testing using a Bruker D2 X-ray diffractometer;

[0063] The scanning electron microscope image of the present invention is obtained by testing using a Phenom ProX scanning electron microscope;

[0064] The discharge performance test in the embodiment of the present invention is carried out using an Autolab PGSTAT 302N electrochemical workstation.

[0065] Example 1

[0066] Add 4mmol ammonium metavanadate (NH4VO3) to 76ml (76g) deionized water, add 4ml (3.6g) ammonia water, mix thoroughly by magnetic stirring, then add 20mmol thioacetamide (TAA, CH3CSNH2), continue stirring until completely dissolved, and obtain a light yellow clear solution with a pH value of 10.2. Transfer it to a 100ml polytetrafluoroethylene reactor, seal it and place it in a blast drying oven with a set temperature of 160℃ for 24 hours. After the reactor is cooled to room temperature, collect the black precipitate in the reactor and wash it alternately with deionized water and anhydrous ethanol for 3 times. Dry the obtained precipitate at 80℃ in a drying oven for 20h to obtain the VS2 product. The diameter range of the lamellae flower ball structure of the product is 7-9μm; the interlamellar spacing range of the lamellae is 0.2-2μm.

[0067] The X-ray diffraction (XRD) pattern of the vanadium disulfide thermal battery positive electrode material of Example 1 is as follows: Figure 1 As shown, from Figure 1It can be seen that the material crystal form of the vanadium disulfide thermal battery positive electrode material prepared in Example 1 has a high degree of match with the VS2 standard card, the crystal form is complete, and no other impurities are generated.

[0068] The scanning electron microscope (SEM) image of the vanadium disulfide thermal battery positive electrode material of Example 1 is as follows: Figure 2 As shown, from Figure 2 It can be seen that the vanadium disulfide material has an obvious lamellar structure, the diameter of the lamellar flower-shaped structure ranges from 7 to 9 μm, and the interlayer spacing of the lamellar ranges from 0.2 to 2 μm.

[0069] Preparation of solid LiF-LiCl-LiBr ternary all-lithium electrolyte:

[0070] Solid LiF (5.26 g), solid LiCl (12.1 g), solid LiBr (37.64 g) and solid MgO (45 g) are uniformly mixed at room temperature and pressure to obtain a solid LiF-LiCl-LiBr ternary all-lithium electrolyte. Based on the total weight of the solid LiF-LiCl-LiBr ternary all-lithium electrolyte as 100%, the contents of solid LiF, solid LiCl, solid LiBr and solid MgO in the solid LiF-LiCl-LiBr ternary all-lithium electrolyte are 5.26%, 12.1%, 37.64% and 45%, respectively.

[0071] In this embodiment, lithium silicon alloy powder is used as the negative electrode, solid LiF-LiCl-LiBr ternary all-lithium electrolyte, vanadium disulfide positive electrode material and two nickel current collectors (φ16 round pure nickel sheets with a thickness of 1mm) to form a high-voltage long-life thermal battery single cell. A φ16 stainless steel cylindrical mold is used, and 0.2g of negative electrode, 0.35g of electrolyte and 0.2g of positive electrode material are added to the mold in sequence under the inert atmosphere of a glove box (after adding any one of the negative electrode, electrolyte and vanadium disulfide thermal battery positive electrode material to the mold in sequence, they are all flattened with a pressing rod), 11MPa pressure is applied, and the mold is removed after staying for 15s. A nickel current collector is placed on both sides of the cylinder obtained by pressing to obtain a high-voltage long-life thermal battery single cell 1. The single cell is discharged at a constant current of 50mA at 500°C, and the open circuit voltage is 2.7V, the first discharge platform is 2.1V-2.2V, and the cut-off voltage is 1V, and the discharge time is 54.2min.

[0072] Example 2

[0073] Add 5mmol ammonium metavanadate (NH4VO3) to 76ml deionized water, add 4ml ammonia water, mix thoroughly by magnetic stirring, then add 23mmol thioacetamide (TAA, CH3CSNH2), continue stirring until completely dissolved, and obtain a light yellow clear solution with a pH value of 10.3. Transfer it to a 100ml polytetrafluoroethylene reactor, seal it and place it in a blast drying oven with a set temperature of 170℃ for 19 hours. After the reactor is cooled to room temperature, collect the black precipitate in the reactor and wash it alternately with deionized water and anhydrous ethanol for 3 times. Dry the obtained precipitate at 80℃ in a drying oven for 21h to obtain the VS2 product. The diameter of the lamellae flower ball structure of the product ranges from 5 to 10μm; the interlamellar spacing of the lamellae ranges from 0.1 to 2μm. In this embodiment, lithium silicon alloy powder is used as the negative electrode, a solid LiF-LiCl-LiBr ternary all-lithium electrolyte (the same as the solid LiF-LiCl-LiBr ternary all-lithium electrolyte used in Example 1), a vanadium disulfide positive electrode material and two nickel current collectors (φ16 circular pure nickel sheets with a thickness of 1 mm) are used to form a high-voltage and long-life thermal battery cell. A φ16 stainless steel cylindrical mold was used, and 0.2 g of negative electrode, 0.35 g of electrolyte and 0.2 g of positive electrode material were sequentially added into the mold under an inert atmosphere of a glove box (after adding any one of the negative electrode, electrolyte and vanadium disulfide thermal battery positive electrode material into the mold in sequence, they were all flattened with a pressing rod), a pressure of 12 MPa was applied, and the mold was removed after staying for 16 seconds. A nickel current collector was placed on each side of the cylinder obtained by pressing to obtain a high-voltage and long-life thermal battery single cell 2. The single cell was discharged at a constant current of 50 mA at 500°C, with an open circuit voltage of 2.71 V, a first discharge platform of 2V-2.3 V, and a discharge time of 58 min when the cut-off voltage was 1 V.

[0074] Example 3

[0075] Add 6mmol ammonium metavanadate (NH4VO3) to 76ml deionized water, add 4ml ammonia water, mix thoroughly by magnetic stirring, then add 25mmol thioacetamide (TAA, CH3CSNH2), continue stirring until completely dissolved, and obtain a light yellow clear solution with a pH value of 10.3. Transfer it to a 100ml polytetrafluoroethylene reactor, seal it and place it in a blast drying oven with a set temperature of 160℃ for 24 hours. After the reactor is cooled to room temperature, collect the black precipitate in the reactor and wash it alternately with deionized water and anhydrous ethanol for 3 times. Dry the obtained precipitate at 80℃ in a drying oven for 23h to obtain the VS2 product. The diameter range of the lamellae flower ball structure of the product is 6 to 11μm; the interlamellar spacing range of the lamellae is 0.2 to 3μm. In this embodiment, lithium silicon alloy powder is used as the negative electrode, solid LiF-LiCl-LiBr ternary all-lithium electrolyte (the same as the solid LiF-LiCl-LiBr ternary all-lithium electrolyte used in Example 1), vanadium disulfide positive electrode material and two nickel current collectors (φ16 round pure nickel sheets with a thickness of 1 mm) to form a high-voltage long-life thermal battery single cell. A φ16 stainless steel cylindrical mold is used, and 0.2g of negative electrode, 0.35g of electrolyte and 0.2g of positive electrode material are added to the mold in sequence under the inert atmosphere of a glove box (after adding any one of the negative electrode, electrolyte and vanadium disulfide thermal battery positive electrode material to the mold in sequence, they are all flattened with a pressing rod), a pressure of 10MPa is applied, and the mold is removed after staying for 18s. A nickel current collector is placed on both sides of the cylinder obtained by pressing to obtain a high-voltage long-life thermal battery single cell 3, which is discharged at a constant current of 50mA at 500°C, and the open circuit voltage is 2.69V. The first discharge platform is 2.1V-2.2V, and when the cut-off voltage is 1V, the discharge time is 55min.

[0076] Comparative Example 1

[0077] A thermal battery monomer cell is composed of lithium silicon alloy powder as the negative electrode, solid LiF-LiCl-LiBr ternary all-lithium electrolyte (the same as the solid LiF-LiCl-LiBr ternary all-lithium electrolyte used in Example 1), iron sulfide material (FeS2) and two nickel current collectors (φ16 round pure nickel sheets with a thickness of 1 mm). A φ16 stainless steel cylindrical mold is used, and 0.2g of negative electrode, 0.35g of electrolyte and 0.2g of positive electrode material are added to the mold in sequence under the inert atmosphere of a glove box (after adding any one of the negative electrode, electrolyte and vanadium disulfide thermal battery positive electrode material to the mold in sequence, they are all flattened with a pressing rod), 11MPa pressure is applied, and the mold is removed after staying for 15s. A nickel current collector is placed on both sides of the cylinder obtained by pressing to obtain a thermal battery monomer cell. The monomer cell is discharged at a constant current of 50mA at 500°C, and the first discharge platform is 1.7-1.8V. When the cut-off voltage is 1V, the discharge time is 62min.

[0078] The comparison of the discharge curves of the thermal battery prepared by using vanadium disulfide as the positive electrode material of the thermal battery in Example 1 of the present invention and the thermal battery prepared by using iron sulfide material (FeS2) as the positive electrode material of the thermal battery in Comparative Example 1 at 500°C at a constant current of 50mA is shown in the figure below. Figure 4 As shown, from Figure 4 It can be seen that the voltage platform (2.2V) of the thermal battery prepared with vanadium disulfide as the positive electrode material of the thermal battery is significantly higher than the voltage platform (1.8V) of the thermal battery prepared with iron sulfide material (FeS2) as the positive electrode material of the thermal battery, and the discharge time is also longer, which meets the requirements of high-voltage thermal battery positive electrode materials.

[0079] It can be seen from Examples 1-3 and Comparative Example 1 that the thermal battery single cell prepared with the vanadium disulfide positive electrode material of the present invention has a stable constant current discharge voltage and a long time. Compared with conventional FeS2, the vanadium disulfide positive electrode material of the present invention is more suitable as a positive electrode material for high-voltage and long-life thermal batteries.

[0080] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A high-voltage and long-life thermal battery single cell, which is prepared from a negative electrode, an electrolyte, a vanadium disulfide thermal battery positive electrode material and a nickel current collector; The vanadium disulfide thermal battery positive electrode material has a lamellar flower ball structure, which is composed of concave hexagonal self-polymerization; the diameter of the lamellar flower ball structure ranges from 4 to 12 μm; The preparation method of the vanadium disulfide thermal battery positive electrode material comprises: The sulfur source, the vanadium source, the alkali regulator and the deionized water are mixed evenly and reacted, and then the reactants are collected, washed alternately with deionized water and an organic solvent, and then dried to obtain the vanadium disulfide thermal battery positive electrode material; The sulfur source is at least one of thioacetamide and sodium thiosulfate; the vanadium source is at least one of sodium orthovanadate and ammonium metavanadate; the alkali regulator is at least one of ammonia water, sodium hydroxide solution, and sodium carbonate solution; the organic solvent is anhydrous ethanol or carbon disulfide; the alkali regulator adjusts the pH of the reaction system to 10-11; the molar ratio of the sulfur source to the vanadium source is 3:1-8:1; the mass ratio of the vanadium source to deionized water is 1:100-1:180; the reaction temperature is 150-200°C, and the reaction time is 19-25 hours; The negative electrode is at least one of lithium silicon alloy powder and lithium boron alloy powder; The electrolyte is at least one of a solid LiF-LiCl-LiBr ternary all-lithium electrolyte and a solid LiF-LiCl-KCl ternary electrolyte; The nickel current collecting sheet is a pure nickel sheet; The mass ratio of the negative electrode to the vanadium disulfide positive electrode material is 1:1 to 1.5:1; The mass ratio of the electrolyte to the vanadium disulfide positive electrode material is 1.5:1-2:

1.

2. The high voltage and long life thermal battery cell according to claim 1, characterized in that: The diameter of the spherical structure of the lamellar flower is in the range of 6 to 10 μm.

3. The high voltage and long life thermal battery cell according to claim 1, characterized in that: The pure nickel sheet is a φ16 round pure nickel sheet with a thickness of 0.01-2 mm.

4. A method for preparing a high voltage and long life thermal battery cell as claimed in any one of claims 1 to 3, characterized in that The method comprises: In an inert atmosphere of a glove box, a negative electrode, an electrolyte, and a vanadium disulfide thermal battery positive electrode material are sequentially added into a cylindrical stainless steel mold, and after being pressed into a cylinder, nickel current collectors are placed on both sides of the cylinder to obtain the high-voltage and long-life thermal battery single cell.

5. The preparation method according to claim 4, characterized in that: The cylindrical stainless steel mold is a φ16 stainless steel cylindrical mold; and / or, The pressure of the compression molding is 10-12 MPa, and the time is 10-20 seconds.

Citation Information

Patent Citations

  • Vanadium disulfide / graphene composite material and preparation method therefor

    CN105355865A

  • Graphene-modified vanadium disulfide micrometer flower material, preparation method thereof and application of graphene-modified vanadium disulfide micrometer flower material as aluminum ion battery cathode material

    CN107482161A

  • Preparation method of hollow flower-ball-like vanadium disulfide

    CN109704405A